15x minus 8=minus 180 3x+8=24
x³ + x² - 3x - 3 = (x + 1)(x + √3) (x - √3).
To factorize the expression 6x^2 - 15x, we first look for the greatest common factor, which in this case is 3x. We can factor out 3x from both terms, resulting in 3x(2x - 5). Therefore, the factored form of 6x^2 - 15x is 3x(2x - 5).
18x2 + 15x + 2 = (3x + 2)(6x + 1)
3x2 - 15x + 42 = 3*(x2 - 5x + 14) which cannot be factorised further.
15x minus 8=minus 180 3x+8=24
3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)
(x + 2)(3x - 1)(3x + 1)
x³ + x² - 3x - 3 = (x + 1)(x + √3) (x - √3).
3x(56x2-15x+1)
To factorize the expression 6x^2 - 15x, we first look for the greatest common factor, which in this case is 3x. We can factor out 3x from both terms, resulting in 3x(2x - 5). Therefore, the factored form of 6x^2 - 15x is 3x(2x - 5).
3x
3x
3x
5(3x + 2 + y)
5(3x-7)
18x2 + 15x + 2 = (3x + 2)(6x + 1)